2004
DOI: 10.1086/380997
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Multiple Sclerosis Susceptibility to the HLA-DR Locus in African Americans

Abstract: An underlying complex genetic susceptibility exists in multiple sclerosis (MS), and an association with the HLA-DRB1*1501-DQB1*0602 haplotype has been repeatedly demonstrated in high-risk (northern European) populations. It is unknown whether the effect is explained by the HLA-DRB1 or the HLA-DQB1 gene within the susceptibility haplotype, which are in strong linkage disequilibrium (LD). African populations are characterized by greater haplotypic diversity and distinct patterns of LD compared with northern Euro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
232
4
1

Year Published

2004
2004
2009
2009

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 305 publications
(247 citation statements)
references
References 46 publications
10
232
4
1
Order By: Relevance
“…Human leukocyte antigen was not included in this list of candidates for two reasons. First, the role of HLA in this data set is described in detail in Oksenberg et al 6 Secondly, MDR is sensitive to the inclusion of genes of major effect in the analysis, so inclusion of an SNP with a large main effect could prevent the discovery of novel interactions. Table 2 shows the most significant results of the MDR analysis conducted in our sample.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Human leukocyte antigen was not included in this list of candidates for two reasons. First, the role of HLA in this data set is described in detail in Oksenberg et al 6 Secondly, MDR is sensitive to the inclusion of genes of major effect in the analysis, so inclusion of an SNP with a large main effect could prevent the discovery of novel interactions. Table 2 shows the most significant results of the MDR analysis conducted in our sample.…”
Section: Resultsmentioning
confidence: 99%
“…These observations, together with the SNP genotyping results mentioned earlier, indicate that the MS patients and controls used in this study were adequately matched. 6 Medical records of all patients were reviewed by one of the authors (SLH or BACC) and in all cases diagnosis was confirmed using McDonald criteria. 32 Ascertainment protocols, and clinical and demographic characteristics are summarized elsewhere.…”
Section: Sample Populationmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent study of DRB1 and DQB1 alleles and haplotypes in a large and wellcharacterized African-American MS cohort, a selective association with HLA-DRB1*15 was revealed, indicating a primary role for the DRB1 locus in MS independent of DQB1*0602. 43 It is then likely that HLA-DRB1 constitutes the centromeric boundary of the class II DR-DQ association in MS. African-American patients also exhibited an unusual high degree of allelic heterogenity as disease association at the DRB1 locus was found for DRB1*1501, DRB1*1503, and DRB1*0301 alleles. The haplotypic features of the DRB1*1501-DQB1*X (non 0602) and DRB1*1503-positive chromosomes indicated an older African origin for the HLA-associated MS susceptibility gene(s), predating the divergence of human ethnic groups, rather than being solely due to genetic admixture with people of European descent.…”
Section: Rr-ms Sp-msmentioning
confidence: 99%